EVALUASI PROGRAM PENDIDIKAN DI MADRASAH IBTIDAIYAH KOTA BENGKULU: DAMPAK TERHADAP PRESTASI SISWA - Hidayaturrahman, M.; Puspita Sari, Dewi; Styo Wati, Sri Sugita; Fusvita, Della; Mardiani, Yena (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
This research aims to evaluate the educational program implemented at Madrasah Ibtidaiyah Bengkulu City and analyze its impact on student achievement. Using a quantitative approach, this research analyzes data collected through questionnaires given to students and teachers as well as interviews with madrasa heads. The research results show that the educational program implemented at Madrasah Ibtidaiyah Bengkulu City has had a positive impact on increasing student achievement. However, several problems, such as limited facilities, still need to be improved to support better quality education. This research suggests that local governments and madrasas improve the quality of teacher training and educational facilities.